The medical complications of binge eating disorder in «Los panecitos de San Nicolás» - Cabrera Ojeda, Sammantha Brizette (2022)
This article will cover the history, symptomatology, diagnosis, treatment, associated factors and possible medical complications of binge eating disorder that may be caused by overweight and obesity in different age and population groups. An analysis of the presence of this disorder in the COVID-19 pandemic will also be presented. The research is based on a possible case of this eating disorder caused by eating too much food, which is narrated in the story «Los panecitos de San Nicolás», which forms part of the book Tradiciones peruanas, a collection of stories written by Ricardo Palma.